2019
DOI: 10.1016/j.bjorl.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Is fine needle aspiration biopsy reliable in the diagnosis of parotid tumors? Comparison of preoperative and postoperative results and the factors affecting accuracy

Abstract: Fine needle aspiration biopsy is an important diagnostic tool for evaluating parotid gland tumors. It is more accurate in detecting benign tumors. In tumors greater than 2cm and extending to the deep lobe, the sensitivity of fine needle aspiration biopsy is high. The use of fine needle aspiration biopsy in conjunction with clinical and radiological evaluation may help to reduce false positive and false negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
3
28
2
3
Order By: Relevance
“…As for determining the "malignant" category, we think that pre-MSRSGC era dichotomous benign/ malignant classification is insufficient to make a differential diagnosis. The sensitivity rate we reported for the diagnosis of malignancy remains low, which is consistent with the literature 26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…As for determining the "malignant" category, we think that pre-MSRSGC era dichotomous benign/ malignant classification is insufficient to make a differential diagnosis. The sensitivity rate we reported for the diagnosis of malignancy remains low, which is consistent with the literature 26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the most common benign tumor was pleomorphic adenoma while the most common malignant was squamous cell carcinoma in compatible with Bachar et al [32]. However, Naeem et al [28] and Altin et al [30] reported mucoepidermoid carcinoma as the most common malignant tumor.…”
Section: Discussionsupporting
confidence: 89%
“…Along Suzuki et al's study, sensitivity, specificity, and accuracy were calculated as 82.3%, 98.7%, and 95.9% respectively [29]. Altin et al showed sensitivity, specificity, and accuracy of 68.96%, 89.63%, and 86.52% [30]. Feinstein et al showed sensitivity of 75% and specificity of 95.1% [31].…”
Section: Discussionmentioning
confidence: 98%
“…The diagnostic difficulty was also caused by the malignant component being too small and elusive in gross specimen even in histopathological examination (5). Another retrospective study by Verma further underscores this pitfall concerning fine needle cytology among malignant parotid tumors (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…This study reported a false negative rate of 15% among parotid malignancies in post operative histopathological diagnosis however there was no variant of MECxPA in this study. Role of core biopsies in parotid neoplasm are dealt with caution as the high risk of tumor seeding or tumor spillage renders grave prognosis hence the advocacy for parotidectomy with adequate margins in suspected malignancies (9).…”
Section: Discussionmentioning
confidence: 99%